2017
DOI: 10.1097/mph.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Approach to Characterize Novel and Cryptic Chromosome Abnormalities in Childhood Myeloid Malignances of Fanconi Anemia

Abstract: Myeloid malignancies can be either primary or secondary, whether or not a specific cause can be determined. Fanconi anemia (FA), a rare constitutional bone marrow failure, usually presents an increased possibility of clonal evolution, due to the increase in chromosomal instability, TP53 activation, and cell death. The evolution of FA may include aplastic anemia by the progressive failure of the bone marrow and myelod neoplasias, such as acute myeloid leukemia and myelodysplastic syndrome. Chromosome abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Borges et al . 24 reported four patients with FA undergoing transformation to MDS (three cases) and AML (one case) who showed chromosomal changes in the BM, one being recurrent and the others, new translocations. Acquired chromosomal changes are the main indication for BM transplantation and the main changes described are losses and gains in the 1q, 3q, and 11q regions, as well as in -7 and +8.…”
Section: Discussionmentioning
confidence: 99%
“…Borges et al . 24 reported four patients with FA undergoing transformation to MDS (three cases) and AML (one case) who showed chromosomal changes in the BM, one being recurrent and the others, new translocations. Acquired chromosomal changes are the main indication for BM transplantation and the main changes described are losses and gains in the 1q, 3q, and 11q regions, as well as in -7 and +8.…”
Section: Discussionmentioning
confidence: 99%
“…Tespit ettiğimiz -7, +8, -20 bulguları, literatürde AA hastalarında görülen kromozom düzensizlikleri olarak bildirilmiştir. [11][12][13][14] Özellikle monozomi 7 ve trizomi 8'in en sık gözlenen kromozom sayı düzensizlikleri olduğu çeşitli çalışma grupları tarafından bildirilmiştir. 14,15 dir.…”
Section: Discussionunclassified
“…In our study, the FISH analysis also showed the monoallelic loss of the KMT2A gene. The KMT2A locus is involved in more than 60 different chromosomal translocations in pediatric acute leukemias [ 17 ]. In AML, the t(9;11) usually results from KMT2A gene translocation, being the (p22;q23) the breakpoint frequently described [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ATM gene acts on the regulation of the cell cycle after a DNA damage is recognized [ 15 , 16 ]. On the other hand, the KMT2A gene encodes a protein that is involved in chromatin remodeling and positively regulates multiple homeobox transcription factors, also it is highly associated with the development of AML [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation